Phytoconstituents of Sansevieria suffruticosa N.E.Br. Leaves and Its Hepatoprotective Effect via Activation of the NRF2/ARE Signaling Pathway in an Experimentally Induced Liver Fibrosis Rat Model. Issue 4 (24th March 2022) - Abdel‐Rahman, Rehab F.; Fayed, Hany M.; Ogaly, Hanan A.; Hussein, Rehab A.; Raslan, Mona A.
Abstract: Sansevieria species possess antioxidant and hepatoprotective activities. However, the therapeutic potential of Sansevieria suffruticosa N.E.Br. in liver fibrosis was not evaluated yet. Twenty‐seven phytoconstituents were tentatively identified in the phytoconstituents profile of Sansevieria suffruticosa N.E.Br. leaves extract (SSLE) using high‐performance liquid chromatography coupled with mass spectrometry (HPLC‐ESI/MS‐MS). Using column chromatography, hesperetin, 4‐hydroxybenzoic acid, ginsenoside Rg2, and quinic acid were isolated from SSLE. The hepatoprotective effect of SSLE via the activation of the NRF2 signaling pathway was evaluated using a rat model of thioacetamide‐induced liver fibrosis. Five groups of 6 male adult Wistar rats were used. All animals except the normal control were injected with 200 mg/kg of TAA intraperitoneally twice weekly for 6 weeks. SSLE‐treated groups were orally administered 200 and 100 mg/kg/day of the extract, two weeks before the liver fibrosis induction and were continued concomitantly with TAA injection. A reference group received 100 mg/kg b.wt of silymarin orally. SSLE treated groups exhibited a marked reduction in serum alanine transaminase (ALT), aspartate transaminase (AST) and malondialdehyde (MDA) levels compared with the TAA group. The levels of reduced glutathione (GSH) content and hepatic mRNA levels of Nrf2 and HO‐1 were significantly increased. Histological findings further confirmed the protective role of SSLE against TAA. In conclusion, the aforementioned results indicated that the hepatoprotective mechanism of SSLE was exerted via activating the Nrf2 pathway to counteract oxidative stress. Abstract :